2015
DOI: 10.1158/1078-0432.ccr-14-0891
|View full text |Cite
|
Sign up to set email alerts
|

Real-time, Near-Infrared Fluorescence Imaging with an Optimized Dye/Light Source/Camera Combination for Surgical Guidance of Prostate Cancer

Abstract: Purpose: The prostate-specific membrane antigen (PSMA) is a surface glycoprotein overexpressed on malignant prostate cells, as well as in the neovasculature of many tumors. Recent efforts to target PSMA for imaging prostate cancer rely on suitably functionalized low-molecular-weight agents. YC-27 is a low-molecular-weight, urea-based agent that enables near-infrared (NIR) imaging of PSMA in vivo. Experimental Design: We have developed and validated a laparoscopic imaging system (including an opt… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 31 publications
1
55
0
Order By: Relevance
“…There remains an unmet clinical need to improve surgical techniques for identifying and removing cancerous tissue without damaging surrounding tissues during prostatectomy. Recently, Neuman and colleagues showed that the near-infrared (NIR) fluorescence probe YC-27 can improve the surgical treatment of prostate cancer and reduce the rate of positive surgical margins in real-time laparoscopic extirpative surgery (17).…”
Section: Introductionmentioning
confidence: 99%
“…There remains an unmet clinical need to improve surgical techniques for identifying and removing cancerous tissue without damaging surrounding tissues during prostatectomy. Recently, Neuman and colleagues showed that the near-infrared (NIR) fluorescence probe YC-27 can improve the surgical treatment of prostate cancer and reduce the rate of positive surgical margins in real-time laparoscopic extirpative surgery (17).…”
Section: Introductionmentioning
confidence: 99%
“…37 Despite the recent advancement in nuclear medicine-based therapy, surgical resection remains a definitive treatment for prostate cancer. 1,8 Compared to PSMA-targeted nuclear medicine, optical imaging could provide real-time guidance during prostate resection with highly sensitive, rapid, and non-radioactive NIR fluorescence light, and importantly, highlight areas of extracapsular extension or in-transit metastases. 79 However, surgery is performed without intraoperative image guidance because there are no clinically available optical contrast agents to help the surgeon ensure clean tumor margins and find small occult metastases in the surgical field.…”
mentioning
confidence: 99%
“…Use of this probe in surgical resection has not been reported. More recently, Neuman et al reported the use of a low-molecular-weight NIR fluorescent agent (YC-27) that targets PSMA in preclinical models of prostate cancer (13, 35). Survival surgery in a mouse subcutaneous xenograft model comparing white light to real-time fluorescent was performed 20 hours post injection, with no recurrence in the fluorescent group (0/8).…”
Section: Discussionmentioning
confidence: 99%